Effects of Li doping and point defect on the magnetism of ZnO. Issue 2 (1st February 2018) - Hou, Qingyu; Jia, Xiaofang; Xu, Zhenchao; Zhao, Chunwang; Qu, Lingfeng
Abstract: The magnetism sources and magnetic mechanism of Li doping and point defect, which coexist in the presence of hexagonal wurtzite ZnO, are controversial. To solve these problems, the effects of Li doping and point defect on the magnetism of ZnO were studied using geometry optimization and energy calculation based on the first-principle generalized gradient approximation + U (GGA + U) method of density functional theory. Results showed that the coexistence of Li doping and Zn vacancy can achieve ferromagnetic long-range order, and the Curie temperature of the doping system can achieve room temperature. In addition, results showed that magnetic moments are significantly different when the structures of the systems are also different with the same doping amount and doping method, which are advantageous for the enhancement of the magnetic properties of dilute magnetic semiconductors. The magnetism source of Zn14 LiO16 is the hybrid coupling electron exchange effect between O-2p and Zn-3d orbits. With the coexistence of Li replacing Zn and Zn vacancy, the closest relative distance between doping and vacancy leads to the lowest formation energy and highest stability. In the condition of the highest stability of the ground state, all the doping systems of Li replacing Zn and O vacancy, doping system of interstitial Li and Zn vacancy, and doping system with the coexistence of Li replacing Zn, interstitial Li, and Zn vacancy are non-magnetic, which are considered worthless in the design and preparation of diluted magnetic semiconductors (DMSs).